2001
DOI: 10.1272/jnms.68.186
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Spondyloepiphyseal Dysplasia Congenita.

Abstract: Spondyloepiphyseal dysplasia congenita (SED) is a rare form of skeletal systemic disease, characterized by congenital dwarfism with a short trunk and epiphysial dysplasia in the long bones and vertebral bodies. Patients also frequently suffer from atlanto-axial instability due to os odontoideum. Compression of the spinal cord caused by atlanto-axial instability is a common, serious complication in SED patients, and causes severe spinal cord symptoms or occasionally sudden death. We present an SED patient who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…There are numerous syndromes that present with a combination of dwarfism and CVJ anomalies. [45678910111213141516] These are all distinct syndromes with easily recognizable clinical features and/or skeletal changes. Their clinical features are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous syndromes that present with a combination of dwarfism and CVJ anomalies. [45678910111213141516] These are all distinct syndromes with easily recognizable clinical features and/or skeletal changes. Their clinical features are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Although os odontoideum was found in all reported individuals with SEDC, only 35% to 60% of them had atlanto-axial instability (Gembun et al, 2001). It was reported that all SEDC-diagnosed individuals with spinal canals #10 mm diameter in the sagittal plane may develop symptoms related to the spinal cord (Nakamura et al, 1998 Tofield and Mackinnon (2003) suggested using a Ferno vacuum splint for neck stability of a patient with SEDC during the operation to repair the cleft palate.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, special equipment is not needed for intubation of patients with SEDC. Gembun et al (2001) resolved the atlanto-axial dislocation in an adult patient with signs of spinal cord compression by using an iliac bone graft. However, the patient's neurological sequelae had partly reversed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spondylo-epiphyseal dysplasia (SED) is a rare heterogeneous form of skeletal systemic disease characterized by congenital dwarfism with a short trunk, and epiphyseal dysplasia in the long bones and vertebral bodies. [1] It results in stunting of growth and premature degenerative arthropathy, due to incongruity of joint surfaces. The underlying defect lies in type II collagen and is classified into two clinical types namely SED congenita and SED tarda.…”
Section: Introductionmentioning
confidence: 99%